Combination of metformin and 9-cis retinoic acid increases apoptosis in C6 glioma stem-like cells. Issue 5 (May 2018) - Songthaveesin, Chanchai; Sa-nongdej, Wanna; Limboonreung, Tanapol; Chongthammakun, Sukumal
Abstract: Glioblastoma (GBM) is the most commonly diagnosed type of brain cancer and the leading cause of brain cancer-related death. GBM contains a subpopulation of tumor-propagating glioblastoma stem-like cells that are thought to drive cancer progression and recurrence. Although several clinical trials are ongoing to explore new chemotherapeutic agents to treat GBM, the use of metformin (Met), a first-line drug for type 2 diabetes mellitus, in cancer remains controversial. Here, we show that combining Met with 9-cis retinoic acid (9-cis RA) reduced the proliferation rate of C6-GSCs (glioblastoma stem-like cells) in vitro . The results of flow cytometric analysis showed that treatment with 9-cis RA for 24 h induced 4.5% early and 38.0% late apoptosis in C6-GSCs. Twenty-four hours of Met treatment induced 23.6% early and 33.5% late apoptosis in C6-GSCs. Combination of Met and 9-cis RA treatment significantly increased both early and late apoptosis to 30.4% and 55.4%, respectively. The present findings suggest that not only 9-cis RA but also Met has the potential to induce early and late apoptotic GSCs death by affecting the functional cytoplasmic and nuclear organelles. At the protein level, there was increased cleaved caspase-3 but decreased procaspase-3 expression in Met-, 9-cis RA- and Met+9-cis RA-treated C6 GSCs, as detected by western blotting. The ratio of cleaved caspase-3/procaspase-3 was 1.6 times higher in Met+9-cis RA-treated groups compared to control. Ultimately, a combination of Met and 9-cis RA might be a possible therapeutic target for the treatment of GBM.